Jayadeva's Ratimanjari: Classical Indian Erotology and Relevance in Contemporary Sexology: Ratimanjari karya Jayadeva: Erotologi Klasik India dan Relevansinya dalam Seksologi Kontemporer - Sharma , Pankaj; Dixit, Sanyogeeta A.; Kulkarni, Vaishnavi G.; Shedbale, Susmita D.; Mohammad, Arshad; Magdum, Aishwarya P. (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2025)
Ratimanjari , authored by Jayadeva, is a seminal work in Indian erotology that integrates poetic expression with Vajikarana Tantra, a branch of Ayurveda focused on sexual and reproductive health. This study explores the text's insights on partner dynamics, erogenous zones, and sexual techniques in the context of contemporary sexual medicine. A critical textual analysis of Ratimanjari was conducted alongside classical Ayurvedic texts and Kamasutra to fill the gaps in the existing literature and perspectives on erotology. The study examined Sanskrit terminology, aphoristic content, and historical interpretations to assess the text’s relevance to modern psychosexual health. Ratimanjari classifies sexual archetypes, outlines 16 sexual postures, and identifies erogenous zones. It emphasizes partner compatibility, emotional intimacy, and techniques for enhancing sexual satisfaction. The findings suggest that Ratimanjari provides a nuanced understanding of intimacy beyond physical pleasure, encompassing emotional and psychological dimensions. The classification of sexual archetypes and emphasis on adaptability resonate with modern theories of sexual compatibility and partner responsiveness. Jayadeva’s Ratimanjari remains a valuable text for understanding human sexuality. Integrating its classical wisdom with contemporary sexology can enhance perspectives on sexual health, relational satisfaction, and psychosexual well-being.